THE INFLUENCE OF COMMUNITY-BASED CORPORATE SOCIAL RESPONSIBILITY (CSR) ON TISKA BEACH TOURISM VISITS IN LAMPUNG PROVINCE - Richa Hesti Dewi; Iskandar Ali Alam (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This research delves into an exploration of the intricate interplay between social responsibility, community-based initiatives, and sustainable tourism practices within the picturesque landscape of Lampung province. The focal point of this study revolves around Tiska Beach, a captivating destination that beckons travelers seeking a harmonious blend of nature and recreation. The overarching objective is to unravel the nuanced influence of these factors on visitor loyalty, thereby contributing to the sustainable development of Tiska Beach and its surrounding communities. The research population comprises the diverse array of visitors gracing the shores of Tiska Beach in Lampung, with a meticulously chosen sample size of 100 individuals. Employing the robust analytical tool of multiple linear regression analysis, the study seeks to dissect the multifaceted dynamics at play within the realm of social responsibility, community-based tourism, and the sustainable practices that underpin Tiska Beach's allure. One pivotal facet of this investigation lies in the acknowledgment of corporate social responsibility (CSR) as a driving force shaping the visitor experience. The essence of CSR resonates with the fundamental notion that organizations, particularly businesses, bear a profound responsibility not only towards their patrons but also to the broader environment encompassing all facets of their operations